Pengetahuan, Sikap, dan Perilaku Higiene dan Sanitasi Penjamah Pangan di Taman Tegalega Kota Bandung - Nurani Putri Setya Pratiwi; Winiati P. Rahayu; Siti Nurjanah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2025)
Tegalega Park is one of the well-known tourist destinations in Bandung, renowned for its historical significance. The high number of visitors makes it a potential market for vendors, including street food vendors. Food processors and handlers must maintain proper sanitation and hygiene to prevent microbial contamination and ensure food safety. This study aimed to assess the knowledge, attitudes, and hygiene and sanitation practices of food handlers in Tegalega Park, examine the correlation between these factors, and propose recommendations for improvement. A survey methodology was employed, with food handlers as respondents. Questionnaires were distributed directly in printed form, and respondents were selected purposively based on the criteria of being street food vendors operating in Tegalega Park. A total of 154 qualified respondents participated in the study. The results indicated that food handlers demonstrated good knowledge, attitudes, and hygiene and sanitation practices, with scores of 53.90% for knowledge, 54.55% for attitudes, and 57.79% for hygiene and sanitation practices (all ≥70% threshold). Respondent characteristics, including age, education level, work experience, and training experience, showed a positive correlation with knowledge, attitudes, and hygiene and sanitation practices. The correlation between attitudes and practices was stronger than that between knowledge and attitudes or knowledge and practices. Overall, there is still a need to enhance knowledge, attitudes, and practices through the equitable distribution of cleaning facilities and targeted counselling or training programs.